Fatigue is associated with cerebral white matter hyperintensities in patients with systemic lupus erythematosus. Issue 2 (14th September 2007) - Harboe, E; Greve, O J; Beyer, M; Gøransson, L G; Tjensvoll, A B; Maroni, S; Omdal, R
Abstract : Background: Fatigue is a disabling phenomenon in many patients who have systemic lupus erythematosus (SLE). The pathophysiological processes are unknown, and no known biological disease factors influence the phenomenon. Because depressive mood is consistently associated with fatigue, and drug treatment for SLE does not ameliorate fatigue, a psychological explanation could be an alternative. In search of a somatic basis for fatigue, we looked for alternative markers of biologic activity associated with fatigue. Cerebral white matter hyperintensities (WMHs) represent biochemical changes of brain tissue and are frequently encountered in patients with SLE, and are associated with cognitive impairment in patients with multiple sclerosis. Presence of such an association between fatigue and WMHs in SLE would favour a biological axis to fatigue. Methods: A cross-sectional, case–control study with 62 unselected patients with SLE and 62 age- and gender-matched healthy subjects. Fatigue was evaluated using the Fatigue Severity Scale (FSS) and a fatigue visual analogue scale (VAS). WMHs were rated using Scheltens' method. Results: Greater fatigue and more WMHs appeared in patients with SLE versus healthy subjects. In the full group of patients (n = 62), fatigue VAS was associated with total WMH score (p = 0.009). In subgroup analysis of patients without clinical depression (n = 40), the association with total WMH remained (p = 0.035), whereas this was not the case in the depressed group (n = 18) (p = 0.211). Conclusion: Increased cerebral WMH load is associated with increased fatigue, indicating a biological origin for some portion of fatigue in patients with SLE.